Problem-Based Islamic Religious Education (PBL) Learning to Strengthen Students' Moderate Attitudes and National Insight - Sofia Ratna Awaliyah Fitri; Aan Hasanah; Dewi Sadiah; Asep Nursobah (International Journal of Islamic Educational Research, 2025)
The role of Islamic Religious Education (PAI) teachers in shaping students' religious moderation is highly needed. The very diverse religious diversity in public schools is a challenge for PAI teachers compared to religious-based schools. The purpose of this study is to identify PAI learning based on Problem Based Learning (PBL) to improve students' moderate attitudes and national insight which includes; planning, implementation, evaluation, supporting and inhibiting factors as well as the impact of problem-based PAI learning to shape students' moderate attitudes and national insight. This study uses a qualitative approach using the case study method. Data collection techniques are carried out through interviews, observations and documentation analysis. The data analysis technique uses the Miles and Huberman analysis technique using the ATLAS.ti analysis tool. The results of the study found that: First, PBL learning planning is carried out by; setting learning objectives, compiling learning steps and learning evaluation. Second, implementation is carried out by; orientation stage, guiding stage, developing stage and conclusion stage. Third, evaluation is carried out by; holistic, diagnostic, formative and summative evaluation stages. Fourth, supporting factors include; student involvement, high teacher creativity, student collaborative learning, program collaboration, contextualization of issues in learning, support for infrastructure and school culture. Inhibiting factors include; difficulty in determining relevant problems, time availability, lack of teacher understanding, student diversity, difficulty generating ideas, social and cultural barriers, and resistance to change. Fifth, a moderate attitude is demonstrated by; tolerance, openness, respect for diversity, good ethics in interactions, wasathiyah, social harmony, critical and objective.